2010
DOI: 10.1038/nchembio.338
|View full text |Cite
|
Sign up to set email alerts
|

Glycopeptide-specific monoclonal antibodies suggest new roles for O-GlcNAc

Abstract: Studies of post-translational modification by β-N-acetyl-D-glucosamine (O-GlcNAc) are hampered by a lack of efficient tools such as O-GlcNAc specific antibodies that can be employed for detection, isolation, and site localization. We have obtained a large panel of O-GlcNAcspecific IgG MAbs having a broad spectrum of binding partners by combining three-component immunogen methodology with hybridoma technology. Immunoprecipitation followed by largescale shotgun proteomics led to the identification of more than 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
163
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 157 publications
(168 citation statements)
references
References 36 publications
3
163
0
Order By: Relevance
“…The two most commonly used pan-specific antibodies for detecting O-GlcNAc-modified proteins are CTD110.6 , a mouse IgM antibody raised against the C-terminus of RNA Pol II, and RL2 (Snow et al 1987), a mouse IgG antibody raised against O-GlcNAc-modified components of the nuclear pore complex. Recently, a number of monoclonal IgG antibodies have been introduced for detecting OGlcNAc-modified proteins including 1F5.D6 (14), 18B10.C7(3), and 9D1.E3(10) (Teo et al 2010). These antibodies were raised against a three-component immunogen-containing epitope regions from the casein kinase α-subunit 15, a mouse major histocompatibility complex class II-restricted helper T-cell epitope, and a Toll-like receptor 2 agonist (Teo et al 2010).…”
Section: Immunopurification With Antibodies and Lectinsmentioning
confidence: 99%
See 3 more Smart Citations
“…The two most commonly used pan-specific antibodies for detecting O-GlcNAc-modified proteins are CTD110.6 , a mouse IgM antibody raised against the C-terminus of RNA Pol II, and RL2 (Snow et al 1987), a mouse IgG antibody raised against O-GlcNAc-modified components of the nuclear pore complex. Recently, a number of monoclonal IgG antibodies have been introduced for detecting OGlcNAc-modified proteins including 1F5.D6 (14), 18B10.C7(3), and 9D1.E3(10) (Teo et al 2010). These antibodies were raised against a three-component immunogen-containing epitope regions from the casein kinase α-subunit 15, a mouse major histocompatibility complex class II-restricted helper T-cell epitope, and a Toll-like receptor 2 agonist (Teo et al 2010).…”
Section: Immunopurification With Antibodies and Lectinsmentioning
confidence: 99%
“…Recently, a number of monoclonal IgG antibodies have been introduced for detecting OGlcNAc-modified proteins including 1F5.D6 (14), 18B10.C7(3), and 9D1.E3(10) (Teo et al 2010). These antibodies were raised against a three-component immunogen-containing epitope regions from the casein kinase α-subunit 15, a mouse major histocompatibility complex class II-restricted helper T-cell epitope, and a Toll-like receptor 2 agonist (Teo et al 2010). Like RL2, these antibodies are mouse IgGs and appear to only recognize O-GlcNAc in certain three-dimensional environments.…”
Section: Immunopurification With Antibodies and Lectinsmentioning
confidence: 99%
See 2 more Smart Citations
“…This moiety is a dynamic post‐translational modification of proteins that is involved in many cellular processes and has been linked to major diseases such as diabetes and Alzheimer's disease 5. There is much interest in agents that bind O‐GlcNAc for use in detection and separation methods for modified proteins 6. A few years ago, we reported that the tricyclic receptor 4 (Figure 1) binds the simplest O‐GlcNAc model 2 with K a =630  m −1 , and the O‐GlcNAcylated peptide 3 with K a =1000  m −1 4e.…”
mentioning
confidence: 99%